2022
DOI: 10.3390/ijerph19073952
|View full text |Cite
|
Sign up to set email alerts
|

Is Social Media a New Type of Social Support? Social Media Use in Spain during the COVID-19 Pandemic: A Mixed Methods Study

Abstract: This study examines Spanish adults’ social media use during the COVID-19 pandemic using mixed-methods to assess and understand frequency, context, and changes in social media use during two critical time points in Spain. We conducted semi-structured interviews in April 2020, and two waves of surveys (April 2020, April 2021) among Spanish adults. We coded and analyzed qualitative data related to social media use during the first lockdown period in Spain using Dedoose software; and ran descriptive statistics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 48 publications
7
24
0
Order By: Relevance
“…With the substantial increases in the use of social media, food insecurity, and the digital food environment since the onset of the COVID-19 pandemic, we explored changes in the nature and frequency of messages during and before the pandemic. Similar to research identifying changes in social media use since the onset of the COVID-19 pandemic [ 41 , 42 ], we identified a 10-fold increase in messages related to food insecurity in March through June of 2020 compared to the same months in 2019. The increase in posts may be related to the significant increase in food insecurity in 2020 compared to 2019 [ 1 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…With the substantial increases in the use of social media, food insecurity, and the digital food environment since the onset of the COVID-19 pandemic, we explored changes in the nature and frequency of messages during and before the pandemic. Similar to research identifying changes in social media use since the onset of the COVID-19 pandemic [ 41 , 42 ], we identified a 10-fold increase in messages related to food insecurity in March through June of 2020 compared to the same months in 2019. The increase in posts may be related to the significant increase in food insecurity in 2020 compared to 2019 [ 1 ].…”
Section: Discussionsupporting
confidence: 68%
“…Considering the high rates of food insecurity among NHPI communities prior to the COVID-19 pandemic, these communities have also been disproportionately impacted by the pandemic; thus, recovery efforts to address the needs of NHPI communities is critical [ 43 ]. While we did not assess changes in food insecurity or behavior in this study, social media represents an important aspect of the digital food environment, and could be used to help reduce food insecurity and promote positive health behaviors such as disease management, physical activity, and cooking [ 12 , 41 , 44 ]. Future research is necessary to better understand how social media groups and pages can assist individuals, reduce food insecurity, and promote chronic disease prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…When consumers encounter a life crisis such as a relationship breakup, we argue a brand can potentially provide companionship. In other words, a brand can act as a surrogate for an empathetic other following a relationship breakup, consistent with the premise that consumers perceive brands as exhibiting human-like characteristics (Rosen et al, 2022;Zhang et al, 2020).…”
Section: The Mediating Role Of Perceived Social Supportsupporting
confidence: 75%
“…Consumers often turn to their friends or family for social support, especially in times of need or crisis (Cohen & Wills, 1985; Xu et al, 2015). Consistent with the premise that consumers perceive brands as exhibiting human‐like characteristics (Rosen et al, 2022; Zhang et al, 2020), we expect that consumers can also look to brands for social support. In this article, we therefore propose that a brand can serve as companion to consumers looking for a dependable bond during a crisis.…”
Section: Introductionsupporting
confidence: 74%
“…The other possible explanation for the association between anxiety and interaction with neighbors was the usage of social media during the lockdown period. Various papers have showed that social media use is an emotional resource for social support in times of crisis or isolation [ 45 ]. Social media platforms were accessible to every individual, allowing them to share, post, and react to any medical information regarding the pandemic [ 46 ].…”
Section: Discussionmentioning
confidence: 99%